HUMANIZATION AS A PROCESS OF THE INTEGRAL MANIFESTATION OF MAN’S SPIRITUALITY IN THE REALITY OF HIS BEING - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article explores the problem of man as a free personality with certain inclinations, identity, life goals and value orientations at the beginning of the XXI c.